2019
DOI: 10.1016/j.eats.2019.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Knotless Separate Layer Transosseous Equivalent Repair of Delaminated Rotator Cuff Tears

Abstract: Delamination of rotator cuff tears presents a challenge for surgeons. Recognizing and repairing such a complex tear pattern often require innovative approaches to achieve an anatomic restoration of footprint. In this Technical Note, we described our preferred method that anatomically repairs both layers of delaminated rotator cuff tear separately in a knotless transosseous equivalent technique. Two sutures are placed to the articular layer in a cinch stitch configuration. Then, closed-loop end sutures are pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Similarly, in the context of delaminated cuff tear repair, it has been revealed that the anatomical reduction of the articular layer, specifically the superior capsule, plays a crucial role in determining clinical outcomes [ 44 ]. Therefore, several SDLR techniques that separately suture the superior capsular layer and the bursal tendon layer have been proposed to address the benefits of anatomically restoring the superior capsular layer and minimizing tension mismatch between the tendon layers [ 9 , 17 , 18 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the context of delaminated cuff tear repair, it has been revealed that the anatomical reduction of the articular layer, specifically the superior capsule, plays a crucial role in determining clinical outcomes [ 44 ]. Therefore, several SDLR techniques that separately suture the superior capsular layer and the bursal tendon layer have been proposed to address the benefits of anatomically restoring the superior capsular layer and minimizing tension mismatch between the tendon layers [ 9 , 17 , 18 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroscopy was used to verify complete removal. The rotator cuff defect was repaired with side‐to‐side suturing when there was no footprint involvement ( n = 37), with the single‐row technique when the defect was located at the footprint and was below 2 cm ( n = 23), or with a double‐row transosseous equivalent technique when the defect was located at the footprint and was larger than 2 cm ( n = 38) [8]. Acromioplasty was performed in patients with single‐ or double‐row rotator cuff repair ( n = 61), and coracoacromial ligament release without acromioplasty was performed in patients with side‐to‐side repairs ( n = 37).…”
Section: Methodsmentioning
confidence: 99%